Hubungan Antara Tingkat Otoritas Orang Tua dalam Pengasuhan dan Disiplin Belajar Siswa Kelas IX di MTs AL-Ahsan Kota Bogor - Gusnaeni, Mezena; Milla, Sri Nurul; Hakim, Nurman (IAI Nasional Laa Roiba Bogor, 2025)
The aims of this research are (1) To determine the level of authority that have been by parents of class IX students at MTs Al-Ahsan, Bogor City. (2) To determine the level of learning discipline of class IX students at MTs Al-Ahsan, Bogor City. (3) To find out whether there is a significant relationship between the level of parental authority and the learning discipline of class IX students at MTs Al-Ahsan, Bogor City. This research uses a quantitative approach and uses a correlation method. Data collection was carried out by distributing questionnaires on the level of parental authority and student learning discipline to 162 class IX students at MTs Al-Ahsan, Bogor City. The research results show that: (1) The level of parental authority obtained a total average score of 59.72, indicating that it is included in the high category. (2) The level of learning discipline of class IX students at MTs Al-Ahsan, Bogor City obtained a total average score of 68.32, indicating that they are included in the high category. (3) The results of the product moment correlation test (R= 0.298, Sig (2-tailed) = 0.000), this shows a positive and significant relationship between parental authority and the learning discipline of class IX students at MTs Al-Ahsan, Bogor City. weak or low, so Ha is accepted and Ho is rejected. So, parental authority in parenting is one of the factors that influences whether or not students are disciplined in studying, because parents are actually the closest to their children.